Workshop Peluang Usaha Di Bidang Olahraga Bagi Guru PJOK Kota Kupang - Michael Johannes Hadiwijaya Louk; Al Ihzan Tajuddin; Ronald Dwi Ardian Fufu; Fera Ratna dewi Siagian; Erwin S. Neolaka; I Nyoman Wahyu Esa Wijaya; Salmon Runesi; Lukas Maria Boleng; Jurdan Martin Siahaan (Pusat Riset dan Inovasi Nasional, 2022)
Nowadays, the interest in sports, especially in game sports, is increasing among young people. It has become a habit, and they even feel uncomfortable when they don't play sports, such as futsal and basketball. In line with their increasing passion, the trend regarding sports accessories is also increasing day by day. Thus, more and more people want to show their